Towards a System of Guidance, Assistance and Learning Analytics Based on Multi Agent System Applied on Serious Games - Lotfi Elaachak; Amine Belahbibe; Mohammed Bouhorma (Institute of Advanced Engineering and Science, 2015)
With the revolution that the education field has known concerning the methods of learning and especially the integration of new technology, several new tools have appeared to replace the tools already existing, and among them there are serious games, serious games as new tool dedicated to education have occupied an important place, and replaced other tools often used in the learning process. But in the order that serious games reach the intended objectives and help instructors to achieve their perspectives considered, they must be equipped with a guidance and assistance system that will assist the learners during the progression in the sequence of the video game, and in addition, they must be equipped with a system of learning analytics that will help instructors to improve the learning process and teaching methods according to the learning outcomes and feedbacks of their learners. In this perspective of research and development we will establish in this paper a new system of assistance, guidance and learning analytics based on a multi agent system that will work in tandem with a web-based serious game.